Literary Chronicles of the Qajars’ Epoch - Jafarzade, Gulnar Aqiq (European Journal of Social Science Education and Research, 2020)
Following a historical appraisal and the progress of literature and poetry during the Qajar era, this article focuses on the specific literary environment in nineteenth century. As literature has effect in all areas such as cultural, social and other affairs, it is important to remember that Qajars’ rulers Fathali Shah and Nasiraddin Shah had an influential role in the comprehensive evolution of the literary environment in this period. Literary chronicles covered the works written during Qajar dynasty can be considered the most important sources for researching literary processes. Circle of poets inside and outside of the court led the new founded literary movement “bazgasht” (“Return”), turning to the their predecessors for the inspiration in this period. The most important and wealthy genre of literature were tazkiras (biographical books of anthology), based on the original source materials in Arabian, Persian, and sometimes in Turkish, especially written about poets and poetry.